Early Outcomes After Branched and Fenestrated Endovascular Aortic Repair in Octogenarians. (December 2018) - Makaloski, Vladimir; Kölbel, Tilo; Rohlffs, Fiona; Behrendt, Christian A.; Law, Yuk; Debus, Eike S.; Tsilimparis, Nikolaos
Abstract : Aim: To compare early outcome after complex endovascular aortic repair in octogenarians (age ≥ 80 years) versus non-octogenarians (age < 80 years) treated with fenestrated or branched stent grafts. Methods: Single centre retrospective analysis from a prospectively collected database of all patients undergoing repair with fenestrated or branched stent grafts for para/suprarenal aortic aneurysm, type Ia endoleak after previous endovascular aortic repair, and thoraco-abdominal aortic aneurysm between January 2015 and December 2017. Early all cause mortality, major adverse events, and need for re-intervention were analysed for non-octogenarians (age < 80 years) and octogenarians (age ≥ 80 years) at the time of repair. Results: 207 patients (58 [28%] females) with a median age of 73 years (IQR 68–78) underwent repair with fenestrated or branched stent grafts. There were 169 (81%) non-octogenarians with a median age of 72 years (IQR 65–76) and 38 (19%) octogenarians with a median age of 82 years (IQR 81–84). The number of patients with chronic kidney disease was significantly higher in the octogenarians (63 [37%] vs. 22 [58%], p = .03]. Nineteen patients (9%) died. The early mortality rate was higher in the octogenarians (12 [7%] vs. 7 [18%], p = .06]. Mortality rate was 4% (6/148) for elective and 22% (13/59) for urgently treated patients. Similar rates of post-operative sepsis, stroke, respiratory problems, need for dialysis, and spinal cord injury were found in both groups. Two patients in each group had early stent graft related re-interventions. The octogenarian group had increased post-operative creatinine values (1.0 [0.8–1.4] vs. 1.4 [1.0–1.9], p = .01). After multiple logistic regression, ASA class ≥4 and rupture were independent factors of early all cause mortality. Conclusions: Complex endovascular repair in octogenarians has higher early all cause mortality compared with non-octogenarians. Rupture and higher ASA class of ≥4 are independent predictors for early mortality. Age ≥80 years was found to be an independent predictor for higher early all cause mortality.